Implementation of the “Kamoe Sajan Gata” Innovation Towards the Reduction of Maternal Mortality Rate - Muaddah, Muaddah; Pabidang, Siswanto; Pramana, Cipta (GLOBAL HEALTH SCIENCE GROUP, 2024)
Various efforts have been made by the government to achieve the target of reducing maternal and infant mortality rates in Indonesia, but these efforts have not provided maximum results. MMR and IMR are still far from the expectations achieved, this is influenced and driven by various medical and non-medical factors such as lack of support from husbands and families, customs that are still strongly embedded in society and gender factors that still dominate, one of the breakthrough efforts made by the Jeumpa Health Center is the